The Influence of Inquiry Learning Strategies and Cognitive Style on Mathematics Learning Outcomes of Grade V SD Pematangsiantar - Junita Palupi Gultom; Julaga Situmorang; Juhana Juhana (Mahesa Research Center, 2021)
This study aims to find out the effect of inquiry learning strategies and cognitive styles on mathematics learning outcomes in grade V SD Pematangsiantar. The research method used is the experimental method with a quasi-experimental design 2 x 2 factorial design. In this study, the samples were grouped into two groups. The two groups were used as the experimental group and the control group respectively. The data collection technique was done through pre-test and post-test to the control group and the experimental group. The results of this study indicate that the mathematics learning outcomes of primary school students who are taught with guided inquiry learning strategies are higher than those taught with free inquiry learning strategies with a mean value of 90,50. Mathematics learning outcomes of primary school students who have an independent cognitive style are higher than those who have a dependent cognitive style with an average score of 89. Mathematics learning outcomes of primary school students have an interaction between inquiry learning strategies and dependent cognitive styles with an average score of 79. The mathematics learning outcomes of the students in free inquiry class have an independent cognitive style with an average score of 87. Mathematics learning outcomes of guided inquiry class students have a dependent cognitive style (A1B2) with an average score of 87. Primary students’ mathematics learning outcomes among those taught using Free inquiry learning strategies are no better than students who are taught using guided inquiry learning strategies and Mathematics learning outcomes of primary students among those who have better independent field cognitive style with dependent learning styles